2017
DOI: 10.1002/jmri.25800
|View full text |Cite
|
Sign up to set email alerts
|

Fluid filling of the digestive tract for improved proton resonance frequency shift‐based MR thermometry in the pancreas

Abstract: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:692-701.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Realtime temperature and motion monitoring would play a major role in this treatment procedure. Some online tools have been already proposed to achieve these tasks but it would be needed to evaluate them in this context [15,[37][38][39][40][41]. Future work should include pre-clinical and clinical experiments to demonstrate its in-vivo feasibility with actual HIFU heating.…”
Section: Discussionmentioning
confidence: 99%
“…Realtime temperature and motion monitoring would play a major role in this treatment procedure. Some online tools have been already proposed to achieve these tasks but it would be needed to evaluate them in this context [15,[37][38][39][40][41]. Future work should include pre-clinical and clinical experiments to demonstrate its in-vivo feasibility with actual HIFU heating.…”
Section: Discussionmentioning
confidence: 99%
“…A polyacrylamide spacer with a drop-shaped dome, which displaced the bowels and thereby facilitated acoustic access to the pancreas, was interposed between the HIFU window and the animal (Figure 1). The influence of a similar spacer on the quality of temperature mapping was studied previously by Ferrer et al [73]. A thin layer of degassed and demineralized water was applied to the HIFU window to establish acoustic coupling to the spacer.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical shifts of protons from fatty acid chains (e.g., from the methylene protons) do not significantly change with temperature (see also subsection "Beyond Classical Phase-Based PRF and MR Spectroscopy: New Alternative MRI Thermometry in the Presence of Fat"). Therefore, PRF-based thermometry cannot be applied to fatty tissues but has recently been combined with T 1 -based thermometry to create temperature maps from body regions that contain both aqueous and adipose tissues (Zhang et al, 2019); see also Table S1 iScience Review filling the digestive tract with an appropriate fluid (here, pineapple juice) to exclude the presence of bowel gas close to the tissue volume to be studied (Ferrer et al, 2018). The authors have experimentally shown that, with respiratory gating and motion compensation, but without bowel filling, the standard deviation may amount to about 10 C in the pancreas head, which would lead to problems in treatment evaluation and safety monitoring during thermal therapy.…”
Section: The Methodological Groundwork: Advances In Mrs and Mri Temperature Methodsmentioning
confidence: 99%